2021
DOI: 10.1039/d1ta06594g
|View full text |Cite
|
Sign up to set email alerts
|

High throughput screening of novel tribromide perovskite materials for high-photovoltage solar cells

Abstract: The efficient search for numerous novel mixed perovskite materials for high-performance solar cells raises a strong demand for high throughput screening protocol. The highly efficient composition screening based on high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…22–24 The feasibility and efficiency of high-throughput experiments in the field of lead perovskite photovoltaics were recently demonstrated. 25–30…”
mentioning
confidence: 99%
“…22–24 The feasibility and efficiency of high-throughput experiments in the field of lead perovskite photovoltaics were recently demonstrated. 25–30…”
mentioning
confidence: 99%
“…This result indicates that the introduction of Br − induces the formation of the 3C phase before annealing and reduces the amount of the 2H phase, which promotes homogeneousness during grain growth, thus increasing its crystallinity and decreasing the defect states, leading to an increase in the periodicity of the atomic arrangement and a decrease in disorder in the film, which consistent with the previous results. [58,59] We fabricated devices with conventional n-i-p junctions (ITO/SnO 2 /perovskite/Spiro-OMeTAD/Au, Figure 6a. From the cross sectional SEM (Figure 6b,c), it can be seen that after the incorporation of Br − , the grain size in the vertical direction becomes larger and the grain boundaries are reduced, and the cavities existing at the interface of SnO 2 /perovskite films also disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…7 In recent years, machine learning combined with DFT (ML-DFT) has shown great potential in promoting the design and screening of new electrocatalysts. [8][9][10][11][12] Wan et al investigated the catalytic activity of hundreds of DACs on a Pc substrate via an ML method combined with DFT calculations and successfully demonstrated Ag-MoPc as a promising CO 2 RR electrocatalyst with a U L of only À0.33 V. 13 Ding et al constructed an active learning framework to study the CO 2 RR to HCOOH and found five unexplored experimental DACs with better CO 2 RR activity and selectivity than pure Bi. 14 Yu et al designed a sandwich structure for the CO 2 RR and constructed an ML model to predict and confirm that Rh 2 @DAC has good catalytic performance.…”
Section: Introductionmentioning
confidence: 99%